1992
DOI: 10.2165/00003088-199200221-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temafloxacin and Ciprofloxacin on the Pharmacokinetics of Caffeine†

Abstract: A number of quinolone antibacterial agents, particularly enoxacin, pefloxacin, pipemidic acid and ciprofloxacin, are known to decrease the clearance of methylxanthines. The effects of temafloxacin and ciprofloxacin on the pharmacokinetics of caffeine were therefore compared in a 3-way crossover study in 12 healthy young volunteers. Each volunteer received 183mg once-daily doses of caffeine in conjunction with twice-daily placebo, temafloxacin 600mg and ciprofloxacin 750mg in 3 separate phases according to a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 20 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…The same study found that OFX had negligible influence on caffeine PK parameters. Another study observed an increase in AUC and terminal phase half-life of caffeine by 145% and 115% respectively when co-administered with 1500 mg CIP [288]. The authors recommended that patients receiving CIP restrict their intake of caffeine.…”
Section: Resultsmentioning
confidence: 99%
“…The same study found that OFX had negligible influence on caffeine PK parameters. Another study observed an increase in AUC and terminal phase half-life of caffeine by 145% and 115% respectively when co-administered with 1500 mg CIP [288]. The authors recommended that patients receiving CIP restrict their intake of caffeine.…”
Section: Resultsmentioning
confidence: 99%
“…Study 4: In this double-blind placebo-controlled randomised study of the interaction potential of ciprofloxacin and temafloxacin with caffeine, oral temafloxacin 600mg (n = 12) was administered q12h for 7 days (Mahr et al 1992).…”
Section: Studies and Volunteersmentioning
confidence: 99%
“…Ciprofloxacin is a potent inhibitor of CYP1A2 and a weak inhibitor of CYP3A4 [4,5] . Some npg studies have demonstrated a drug-drug interaction when ciprofloxacin was co-administered with other drugs, including theophylline [6,7] , caffeine [8] , clozapine [9] , methadone [10] and zolpidem [11] . Ciprofloxacin is commonly prescribed with analgesics for the management of infection, pain and inflammation.…”
Section: Introductionmentioning
confidence: 99%